Digital bricolage: Infrastructuring lower carbon digital space via Nordic datacentre development. (June 2022) - Upham, Paul; Sovacool, Benjamin; Monyei, Chukwuka
Abstract: Access to electric power and land are now key locational issues for the datacentre sector and most Nordic countries are pitching for their business. We use a comparative case analysis to illustrate several interrelated themes in Norway and Iceland, as both develop their datacentre sectors, but to date in differing ways. In both, digitalisation and datacentres are supported financially through equity holdings and securitisation issued via bespoke investment firms. For datacentres, this finance backs commoditised packages consisting of land with pre-approved planning permission; access to low-cost, reliable, renewable power; and a range of built infrastructure and computing options. Seeking to benefit from the development of monetised, dependent, regional Information Technology ecosystems, states assist with regulatory adjustments and municipalities with supportive land use zoning. Given the deeply entrained and multifaceted nature of the sector, we use our cases to highlight relationships between datacentre financing, spatial planning and infrastructure development in the two countries and also the ways in which the sector may take differing development trajectories. Overall, we build on the developing literature that is revealing the material realities of 'the cloud'. Highlights: Norway and Iceland are pitching for datacentre business via power, land and climate. A transect across recent infrastructure developments to identify research questions raised. Corporate digitalisation and datacentres supported by bespoke investment firms. Includes commoditised packages of land, planning permission, power and infrastructure. States assist with regulatory adjustments and municipalities with land use zoning.